Black NiO-TiO2 nanorods for solar photocatalysis: Recognition of electronic structure and reaction mechanism - Liu, J.; Li, Y.; Ke, J.; Wang, Shaobin; Wang, L.; Xiao, H. (Elsevier BV, 2018)
This work provides an engineering guide to construct active sites on TiO 2 nanorods (NRs) by coupling p-type black NiO nanoclusters (E g = 1.42 eV) with rich crystal defects and match-up band structure for excellent solar photocatalysis. Photo-oxidation of toluene was used as a model reaction to evaluate the photocatalytic performance of black NiO/TiO 2 hybrids under simulated solar light irradiation from a 300 W Xe-lamp. The black NiO/TiO 2 hybrids Exhibit 80% of photodegradation conversion and 56% of mineralization efficiency, which are 7.9 and 4.5 times higher than those of TiO 2 NRs. Detailed characterizations reveal that highly dispersed NiO and p-n heterojunction effectively facilitate light-harvesting, separation and transfer of photo-generated charge carries, and significantly inhibit the recombination of electrons and holes. Furthermore, the realignment of band structure and the p-n heterojunctions in NiO/TiO 2 result in the production of [rad]O 2 - and h + with a longer lifetime, which could efficiently attack the aromatic ring of toluene. The efficient adsorption of toluene by H-bonding formation also facilitates the photo-oxidation of toluene on NiO/TiO 2 .